Mapping the post-bureaucratic landscape: project managers’ perception of bureaucracy in European Union Cohesion policy projects - Vento, Isak; Kuokkanen, Kanerva (International review of administrative sciences, 2022)
New post-bureaucratic organizational forms, such as projects, are increasingly used in policy implementation. Their assumed benefits in decreasing bureaucracy and increasing flexibility have, however, been questioned. It has been argued that public projects increase red tape (or bureaucracy perceived as a nuisance) because of the formal rules associated with them. Despite the topicality of the subject, we do not know how public project bureaucracy is perceived by the actors involved. This article explores the bureaucracy of public projects by analysing project managers’ perceptions of them with data from European Union Cohesion policy projects in Finland. The data consist of project register data and a survey to project managers (N = 728). The study finds that when talking of the perception of bureaucracy, it is relevant to distinguish between a general attitude towards bureaucracy and a specific perception of the task at hand. The general attitude seems more negative than the specific perception of bureaucracy. We also show that project managers’ experience, institutional background and share of administrative tasks in the project condition the extent to which bureaucracy is perceived as red tape. To conclude, the findings are discussed in relation to previous research on red tape in public administration. Points for practitioners Project organization connotes flexibility and innovation but involves also bureaucracy, which can be received as red tape, especially for inexperienced managers. In general, managers consider project bureaucracy as red tape, while in their own projects, bureaucracy is seen as less burdensome. Public managers have an advantage over managers from non-public organizations by perceiving public project bureaucracy as less burdensome.